SELF-TAUGHT CLOUD COMPUTING ENGINEER a comprehensive professional study guide to AWS, Azure, and GCP - Song, Logan (Packt Publishing Ltd., 2023)
Begin your exploration into cloud computing by developing deep knowledge of cloud technologies, enhancing hands-on skills, and achieving proficiency in cloud Key Features Teach yourself all about cloud computing with this easy-to-follow guide Develop a well-rounded skillset--from fundamentals to data, machine learning, and security Work on real life industrial projects, business use cases, and personal cloud career development Purchase of the print or Kindle book includes a free PDF eBook Book Description This book is an all-inclusive guide for IT professionals to master cloud computing concepts by building a broad and deep cloud knowledge base, developing hands-on cloud skills, and achieving professional cloud certifications. If you're a beginner with basic computer hardware and software understanding, this book provides the means to transitions into a cloud computing career. Starting with a focus on the Amazon cloud, you'll be introduced to fundamental AWS cloud services, followed by advanced AWS cloud services in the domains of data, machine learning, and security. Next, you'll build proficiency in Microsoft Azure cloud and Google Cloud Platform (GCP) by examining the common attributes of the three clouds, differentiating their unique features, along with leveraging real-life cloud project implementations on these cloud platforms. Finally, you'll get guidance on cloud certifications and career development. Walking through this cloud computing book, you'll systematically establish a robust footing in AWS, Azure, and GCP, and emerge as a cloud-savvy professional, equipped with cloud certificates to validate your skills. What you will learn Develop the core skills needed to work with cloud computing platforms such as AWS, Azure, and GCP Gain proficiency in compute, storage, and networking services across multi-cloud and hybrid-cloud environments Integrate cloud databases, big data, and machine learning services in multi-cloud environments Design and develop data pipelines, encompassing data ingestion, storage, processing, and visualization in the clouds Implement machine learning pipelines in multi-cloud environment Secure cloud infrastructure ecosystems with advanced cloud security services Who this book is for Whether you're a beginner in cloud computing or an experienced professional seeking to expand your skills, this meticulously designed study book is for anyone in the information technology domain aiming to thrive in the realm of cloud computing. With this comprehensive roadmap, you'll have the tools to build a successful cloud computing career.